Impact of Supply Chain Capabilities on Supply Chain Performance: A Case of Thai Electronic Industry - Chonmapat Torasa; Witthaya Mekhum (International Journal of Supply Chain Management, 2020)
The present study empirically investigated the supply chain capabilities to determine the supply chain performance in electronic industry of Thailand. Globally, competition has increased due to business expansion and global phenomenon. The study investigated the relationship between supply chain capabilities as measured by supplier partnership and innovativeness in turbulent and highly competitive environment. The current study is conducted on electronic industry of Thailand, to investigate the influence of supplier partnership and supply chain performance and influence of innovation on supply chain performance. The study is unique in determining the moderating role of technology adoption for supply chain between independent variable and dependent variable. The analysis of the study suggested that supplier partnership influence supply chain performance, similarly innovation influence the supply chain performance, moreover moderating effect was also reported and demonstrated in analysis phase of the study by significant change in the effect of independent variables on dependent variables.